2017
DOI: 10.1007/s10803-017-3120-6
|View full text |Cite
|
Sign up to set email alerts
|

Using Time Perception to Explore Implicit Sensitivity to Emotional Stimuli in Autism Spectrum Disorder

Abstract: Establishing whether implicit responses to emotional cues are intact in autism spectrum disorder (ASD) is fundamental to ascertaining why their emotional understanding is compromised. We used a temporal bisection task to assess for responsiveness to face and wildlife images that varied in emotional salience. There were no significant differences between an adult ASD and comparison group, with both showing implicit overestimation of emotional stimuli. Further, there was no correlation between overestimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
0
12
2
Order By: Relevance
“…For example, patients with an autism spectrum disorder who exhibit deficits in the explicit recognition of emotions produce time distortions when confronted with angry faces in the same way as healthy subjects (Jones, Lambrechts, & Gaigg, 2017). Although the effects of emotion on the perception of time in pathological patients have only just started to be investigated, they represent a genuinely new and interesting research direction (e.g., Jones et al, 2017; Ryu, Kook, Lee, Ha, & Cho, 2015). Furthermore, a small number of studies have examined the neural mechanisms involved in emotional time distortions (Dirnberger et al, 2012; Pfeuty, Dilharreguy, Gerlier, & Allard, 2015).…”
Section: Time Distortionsmentioning
confidence: 99%
“…For example, patients with an autism spectrum disorder who exhibit deficits in the explicit recognition of emotions produce time distortions when confronted with angry faces in the same way as healthy subjects (Jones, Lambrechts, & Gaigg, 2017). Although the effects of emotion on the perception of time in pathological patients have only just started to be investigated, they represent a genuinely new and interesting research direction (e.g., Jones et al, 2017; Ryu, Kook, Lee, Ha, & Cho, 2015). Furthermore, a small number of studies have examined the neural mechanisms involved in emotional time distortions (Dirnberger et al, 2012; Pfeuty, Dilharreguy, Gerlier, & Allard, 2015).…”
Section: Time Distortionsmentioning
confidence: 99%
“…While two studies reported decreased duration discrimination in the ASD group (Karaminis et al, 2016;Kargas et al, 2015), other studies testing time bisection (Gil et al, 2012;Jones et al, 2017) and duration discrimination found no differences between ASD and control groups (Jones et al, 2009;Mostofsky et al, 2000). Thus, again performance on interval timing tasks in ASD might depend on task specificities and sampling.…”
Section: Introductionmentioning
confidence: 95%
“…Among such secondary characteristics, difficulties in timing might be a key part of the autistic cognitive profile (e.g., Allman et al, 2011;Bebko et al, 2006;Boucher et al, 2007;Brodeur et al, 2014;Falter et al, 2012a;Falter et al, 2012b;Falter et al, 2013;Gepner & Féron, 2009;Gowen & Miall, 2005;Karaminis et al, 2016;Kargas et al, 2015;Kwakye et al, 2011;Maister & Plaisted-Grant, 2011;Martin et al, 2010;Szelag et al, 2004;Whiting & Dixon, 2015;Ribeiro Zukauskas et al, 2009; for review and clinical discussion, see Allman & Falter, 2015;Boucher, 2001;Falter & Noreika, 2014;Stevenson et al, 2016;Welsh et al, 2005). However, timing deficits in ASD are not unequivocal (e.g., Bebko et al, 2006;Gil et al, 2012;Glazebrook et al, 2008;Jones et al, 2009;Jones et al, 2017;Kwakye et al, 2011;Mostofsky et al, 2000;Wallace & Happé, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of neural impairments in the ASD group was not in line with the initial hypothesis, which, in the absence of fMRI studies of timing in ASD, was formulated based on behavioral findings only [e.g., ( 39 , 42 )]. However, negative neurobehavioral findings from some studies ( 45 47 ), including a recent study in adults with ASD ( 77 ), have suggested heterogeneity in timing impairments in this population. Therefore, although the implication of the present neurofunctional finding is that timing networks in young adults with ASD without intellectual disability are unimpaired, this must be taken mindful of factors that could have increased the participants' heterogeneity in the study.…”
Section: Discussionmentioning
confidence: 98%